Usability Scale to Measure the Acceptability of Interactive Learning Media for Ratio Material in Grade VI - Diki Somantri; Yunus Abidin; Dede Tri Kurniawan; Dinie Anggraeni Dewi (Edu Komputika Journal, 2025)
Mathematics learning, particularly for abstract topics such as ratios, requires a transition from additive to multiplicative thinking, which is often challenging to visualize. To support teachers, an Interactive Learning Media (ILM-Ratio) was developed using Canva to ensure accessibility and ease of content modification. Before measuring student effectiveness, it is crucial to assess the media's technical acceptability from the teachers' perspective, as they are the primary gatekeepers of classroom technology. This study aims to evaluate the usability of ILM-Ratio using the System Usability Scale (SUS). A total of 47 sixth-grade teachers participated by simulating a teaching session using the media. The SUS calculation yielded an average score of 90 (Grade A), categorized as "Excellent." This score indicates that ILM-Ratio possesses high usability and imposes minimal technical burden on teachers. These findings suggest that the media is technically robust and ready for classroom implementation to support the visualization of ratio concepts.